CT imaging features of paranasal sinuses in children with primary ciliary dyskinesia. (2nd December 2022) - Lyu, Huiying; Guo, Zhuoyao; Chen, Chao; Duan, Bo; Xu, Zhengmin; Chen, Wenxia
Abstract: Background: Primary ciliary dyskinesia (PCD) causes impaired mucociliary clearance and results in chronic pulmonary and sinonasal symptoms. Objectives: To study the CT imaging features of paranasal sinuses in children with PCD. Materials and methods: 17 PCD patients ranged from 4 to 13 years, a mean age of 7.9 ± 3.3 years, were included in the final analysis. Patients with non-PCD chronic rhinosinusitis (CRS) who accepted maxillary balloon catheter dilation were included in the control group. Paranasal sinuses CT scans were scored according to the Lund–Mackay staging system. The correlation between age and Lund–Mackay score was analyzed. Results: 100% (17/17) had rhinosinusitis, 52.9% (9/17) had lung consolidation, 64.7% (11/17) had atelectasis, 35.3% (6/17) had bronchiectasis, and 47.1% (8/17) had a history of neonatal respiratory distress. The mean Lund–Mackay score of PCD patients was 14.2 ± 3.1, that of non-PCD CRS patients was 14.6 ± 5.5, the difference was not significant ( p = .79). There was a significant inverse correlation between age and Lund–Mackay score in PCD patients ( r = −0.530, p = .029) but not in non-PCD CRS patients ( r = −0.168, p = .519). Conclusion: Radiographic severity of rhinosinusitis in PCD patients was similar to the control population but decreased with age. Significance: First time to propose radiographic severity of rhinosinusitis in pediatric patients with PCD might decrease with age.